Proposição de um metamodelo de referência para a implementação da gestão de ativos físicos nas organizações - Emerick, Natali da Costa (2019)
Structuring asset management is a challenge for organizations that business standard depends of physical assets for value generation. There have been great strides in discipline in last years, which has spawned an extensive body of knowledge in the field. About the theoretical perspective, several models point out requirements of what must be done for the implementation of an asset management system and, from the practical point of view, few references indicate how these guidelines should be implemented. Then was perceived an interest in the construction of a metamodel that seeks the integration of existing models, a way to facilitate the implementation and maturation of the management of physical assets in organizations. The research method used includes bibliographic research and field research. A systematic review of the literature was done, including gray literature, and technical visits and interviews were conducted to six Brazilian companies that adopt asset management in different stages. As a result, it achieved the characterization of this research area in asset management, the first version of a metamodel for consolidation of knowledge in the field and a set of good practices that materialize the process of adoption of the system by companies.